2003
DOI: 10.1016/s0892-1997(03)00027-4
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Fiber Type Composition and Effects of Vocal Fold Immobilization on the Two Compartments of the Human Posterior Cricoarytenoid: A Case Study of Four Patients

Abstract: SummaryThe human posterior cricoarytenoid (PCA) muscle is divided into two compartments, the vertical and horizontal bellies, which contain differences in their myosin heavy chain (MyHC) composition. Using immunohistochemical techniques on whole PCA samples, this study provides a more thorough description of the fiber type composition of entire bellies of the PCA. Four patients provided complete PCA samples containing both compartments of their right and left sides; two with unilaterally immobilized vocal fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
4
26
1
Order By: Relevance
“…The fiber type distribution, at least in simple muscle spindles in smaller mammals, usually consists of 1 bag1 fiber, 1 bag2 fiber, and 2 or more chain fibers. In previous investigations, we were unable to identify muscle spindles in human PCA 10 and TA 11 muscles. In the current study, however, muscle spindles were easily identified in human IA muscle, at an average of 7 spindles per muscle.…”
Section: Intrafusal Fiber Types and Muscle Spindle Anatomymentioning
confidence: 77%
See 3 more Smart Citations
“…The fiber type distribution, at least in simple muscle spindles in smaller mammals, usually consists of 1 bag1 fiber, 1 bag2 fiber, and 2 or more chain fibers. In previous investigations, we were unable to identify muscle spindles in human PCA 10 and TA 11 muscles. In the current study, however, muscle spindles were easily identified in human IA muscle, at an average of 7 spindles per muscle.…”
Section: Intrafusal Fiber Types and Muscle Spindle Anatomymentioning
confidence: 77%
“…11 Likewise, no spindle structures were identified in the PCA muscle. 10 In the IA muscle, however, we were able to identify muscle spindles easily, at an average of 7 spindles per muscle. Some of these spindles had complex anatomy, in that for part of their length they shared a connective capsule with another spindle.…”
Section: Interarytenoid Muscle Contains Anatomically Complex Muscle Smentioning
confidence: 86%
See 2 more Smart Citations
“…In contrast, the jaw-closing muscles have functions, anatomy and fiber types that vary tremendously between species. Laryngeal muscles have more modest variability in anatomy, perhaps more significant variability in function and their fiber type properties are currently under investigation [Brandon et al, 2003].…”
Section: Introductionmentioning
confidence: 99%